Prevalence and severity of Coronavirus disease 2019 (COVID-19) in Transfusion Dependent and Non-Transfusion Dependent β-thalassemia patients and effects of associated comorbidities: an Iranian nationwide study: Prevalence and severity of COVID-19 in β-thalassemias - Karimi, Mehran; Haghpanah, Sezaneh; Zarei, Tahereh; Azarkeivan, Azita; Shirkavand, Afshan; Matin, Sara; Tavakoli, Maryam Akavan; Zahedi, Zohre; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
Background: Coronavirus disease 2019 (COVID-19) outbreak is a global and challenging disease that is accompany with mortality and morbidity. Aim of study: We evaluated the prevalence and the impact of comorbidities in thalassemia Iranian patients affected by COVID-19.  Methods: A multicenter, retrospective, cross-sectional study was conducted across all comprehensive thalassemia centers in Iran, from January to June 15th, 2020. Results: Forty-three confirmed COVID-19 thalassemia patients (32 TDT, and 11 NTDT) were detected. The mean age of patients was 35.3 ± 11.5 years (range 9 - 67); 21 females and 22 males. Overall, 78.1% of TDT and 90.9% of NTDT patients were complicated with at least one comorbidity (P: 0.656). The overall mortality rate of thalassemia patients with COVID-19 was 18.6% while 27.3% was in NTDT patients compared to 15.6% in TDT patients (P:0.401). The dead group had a non-significant higher frequency of endocrinopathies compared to the recovered group (62.5% versus 45.7% P:0.457). Ten female thalassemia patients with positive COVID-19 had hypogonadism, six patients were receiving hormone replacement therapy and all of them recovered (zero death) compared to two deaths from 4 patients who were not receiving hormone replacement therapy (P:0.133). Furthermore, the prevalence of COVID-19 in NTDT patients was significantly higher than the general population (45 per 10,000 versus 22.29 per 10,000 respectively, P:0.018) while the prevalence of TDT was almost similar to the normal population (P:0.539). The mortality rate of COVID-19 was 4.71% in the normal Iranian population compared to 18.6% in β-thalassemias (P: